2020
DOI: 10.21608/ejchem.2020.43922.2893
|View full text |Cite
|
Sign up to set email alerts
|

Extracts of M. pulegium (L.) and M. spicata(L.): Effect of Extraction Conditions on Phenolics and Flavonoïds Contents and Their Antioxidant Power

Abstract: The correlation between the contents of polyphenols and flavonoïds and the degree of antioxidant activity of various extracts from M. pulegium (L.) and M. spicata (L.), obtained by different solvents and methods, was investigated. The crude extracts were prepared by mixing areal parts in powder with methanol/water solution. They were subjected later to liquid-liquid extraction via solvents with progressive polarity (chloroform, ethyl acetate and n-butanol) by maceration and soxhlet techniques. The total phenol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 36 publications
2
2
0
Order By: Relevance
“…These findings are consistent with literature studies showing how polar extracts (methanol, ethanol or water) from M. spicata contain higher levels of phenolics compared to non-polar extracts [40][41][42]. In these studies, the quantification of phenolic compounds was mainly conducted through colorimetric assays.…”
Section: Total Phenolic and Flavonoid Contentsupporting
confidence: 90%
See 1 more Smart Citation
“…These findings are consistent with literature studies showing how polar extracts (methanol, ethanol or water) from M. spicata contain higher levels of phenolics compared to non-polar extracts [40][41][42]. In these studies, the quantification of phenolic compounds was mainly conducted through colorimetric assays.…”
Section: Total Phenolic and Flavonoid Contentsupporting
confidence: 90%
“…Acetone is a non-toxic solvent that can be easily mixed with water in order to achieve the highest polarity. However, although there are several studies on M. spicata alcoholic and hydroalcoholic extracts [40][41][42], investigations on acetone and acetone/water extracts from M. spicata are limited. Therefore, the present paper aims to gain new knowledge about the choice of extraction solvents with M. spicata.…”
Section: Introductionmentioning
confidence: 99%
“…The aqueous extract yield is noticeably higher at 15.81% compared to the ethanolic and ethyl acetate extracts, which stand at 7.59 and 2.57%. In general, the efficiency of extraction increased with increasing polarities of the solvent used; this result is almost consistent with the extraction yield of Mentha spicata L. (Zekri et al 2020). Polar solvents can diffuse inside the plant powder and recover as many metabolites as possible.…”
Section: Yield Of Extractionsupporting
confidence: 81%
“…Quantitative analysis (mg•g −1 of dry sample) of the main phenolic compounds of MAE extracts from different Mentha species was carried out by HPLC-MS in SIM mode (Table 2). Although several studies can be found in the literature comparing the total phenolic content of extracts (generally obtained by solid-liquid extraction or Soxhlet [46][47][48]) from different Mentha species, studies related to the individual concentration of these compounds determined by HPLC are more limited [19,26,49]. As expected, the composition of the MAE extracts obtained in this work was different, depending on the Mentha species considered.…”
Section: Lc-ms Characterizationmentioning
confidence: 66%